Oral microbial diversity analysis of caries-free and caries-active healthy Filipino adults through the 16s rRNA gene - Reyes, Candids Patrice A. (Transactions of the National Academy of Science and Technology, 2011)
The oral cavity is inhabited by hundreds of bacterial species that play vital roles in maintaining oral health or in shifting to a diseased state like dental caries which is the most common oral problems that affect 92.4% of Filipinos. Due to the limitation that are posted by microbial identification through culture-dependent techniques, molecular techniques are currently being used to better understand the bacterial etiology of dental caries. This study aimed to assess the oral microbial diversity of caries-free and caries-active Filipino adults through the 16S ribosomal ribonucleic acid gene (16s rDNA). Saliva, a supragingival plaque samples from 6 caries-free and 6-caries active adults together with carious teeth samples from the caries-active patients were used. Diversity of the samples were assess using denaturing gradient gel electrophoresis and the microorganisms were identified through sequencing of the 16s rDNA. Identified bacteria from saliva and plaque samples were compared between these groups as well as with carious teeth samples. Based on the gathered data, the caries-free group exhibited a more diverse microflora compared with their caries-active counterpart. Several bacteria were found to be common to both groups compromising the resident microflora. Neisseria subflava and Capnocytophaga species were some of the identified potentially carcinogenic bacteria since they were seen only among the caries-active adults. The partial clone library of the 16S rDNA included various species of Leptotrichia , Streptococcus, and Neisseria. This study showed the oral microbial diversity profile of caries-free and caries-active Filipino adults using culture-independent. The saliva and plaque samples of the caries-free group exhibited greater biodiversity compared with the caries-active group. This result suggests that part of the microflora may be inhibited or absent in a caries-active state.